Comparative study of hexane extract for volatile and non volatile components of leaves and rhizomes of Acorus calamus linn. using high performance thin layer chromatography (HPTLC) - Bisht, AS; Chauhan, Monika; Joshi, A; Joshi, Y; Dimri, A; Singh, V; Juyal, D (Creative Pharma Assent, 2014)
The present communication attempts to evaluate the comparative study of leaves and rhizomes of Acorus calamus Linn. (Family; Araceae) using High Performance Thin Layer Chromatography (HPTLC). Since the plant contains various volatile and non-volatile components so paper advocates the quantitative study using hexane extract. Acorus calamus Linn. is a well known medicinal plant in traditional medical systems having various ethno-pharmacological uses. As the official source of the plant is roots and rhizomes, but here study had been done comparatively with leaves. Previously leaves of Acorus calamus were not regarded as useful part of plant, but recently there is growing interest in leaves of the said plant. The leaves are considered to possess various activities such as an insect repellent, when cut up and kept with grain storage; anti-hyperlipidemic; anti-diabetic; antipsychotic; anti-inflammatory and analgesic. As there is no detailed work reported in leaf constituents of the plant, therefore the study revealed specific quantitative HPTLC data for the plant for future standardization work. HPTLC analysis of both leaves and rhizomes showed the presence of Asarone, β- sitosterol, lupeol and Ursolic acid when matched with marker compounds.